Urtica dioica-Derived Phytochemicals for Pharmacological and Therapeutic Applications. (24th February 2022) - Taheri, Yasaman; Quispe, Cristina; Herrera-Bravo, Jesús; Sharifi-Rad, Javad; Ezzat, Shahira M.; Merghany, Rana M.; Shaheen, Shabnum; Azmi, Lubna; Prakash Mishra, Abhay; Sener, Bilge; Kılıç, Mehtap; Sen, Surjit; et al.
Abstract : Urtica dioica belongs to the Urticaceae family and is found in many countries around the world. This plant contains a broad range of phytochemicals, such as phenolic compounds, sterols, fatty acids, alkaloids, terpenoids, flavonoids, and lignans, that have been widely reported for their excellent pharmacological activities, including antiviral, antimicrobial, antihelmintic, anticancer, nephroprotective, hepatoprotective, cardioprotective, antiarthritis, antidiabetic, antiendometriosis, antioxidant, anti-inflammatory, and antiaging effects. In this regard, this review highlights fresh insight into the medicinal use, chemical composition, pharmacological properties, and safety profile of U. dioica to guide future works to thoroughly estimate their clinical value.